Hydroxytyrosol in functional hydroxytyrosol-enriched biscuits is highly bioavailable and decreases oxidised low density lipoprotein levels in humans. (15th August 2016) - Mateos, Raquel; Martínez-López, Sara; Baeza Arévalo, Gema; Amigo-Benavent, Miryam; Sarriá, Beatriz; Bravo-Clemente, Laura
Highlights: After HT-B intake HT metabolites were identified in plasma and urine. HT in biscuits is extensively metabolized and rapidly eliminated in urine. HT in biscuits is highly bioavailable and reduces postprandial oxidised-LDL levels. Abstract: Hydroxytyrosol (HT) and its derivatives in olive oil protect low-density lipoproteins (LDL) against oxidation. Biscuits could be a convenient alternative to broaden consumers' choice of HT-rich foods, although the biscuit matrix could affect HT bioavailability. We performed a crossover, randomized, double-blind study to evaluate HT bioavailability in HT-enriched biscuits (HT-B) versus non-enriched biscuits (C-B), and the effects on oxidative postprandial status. On two separate days, 13 subjects consumed 30 g of C-B or HT-B (5.25 mg HT) after overnight-fasting. Blood and urine were collected at different intervals and analysed by LC–MS-QToF. After HT-B consumption, plasma metabolites peaked between 0.5 and 1 h and were extensively excreted in urine. HT-sulphate and 3, 4-dihydroxyphenylacetic acid (DOPAC)-sulphate were the main metabolites, followed by DOPAC and homovanillic acid (HVA). HT-glucuronide, DOPAC-glucuronide, HVA-glucuronide and HVA-sulphate were also detected. Postprandial oxidised-LDL concentrations decreased with HT-B. HT is a promising functional ingredient and, in biscuits, it is highly bioavailable and lowers postprandial oxidised-LDL levels.